2007
DOI: 10.2106/jbjs.f.00654
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization in External Rotation After Shoulder Dislocation Reduces the Risk of Recurrence

Abstract: Immobilization in external rotation after an initial shoulder dislocation reduces the risk of recurrence compared with that associated with the conventional method of immobilization in internal rotation. This treatment method appears to be particularly beneficial for patients who are thirty years of age or younger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
161
2
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(181 citation statements)
references
References 15 publications
7
161
2
11
Order By: Relevance
“…In comparison with traditional immobilization in internal rotation, this new method was assumed to reduce the recurrence rate after a first-time traumatic anterior shoulder dislocation. These findings were later supported by Itoi et al [2,3] in an MRI study (2001) and in a randomized controlled study (2007) in which a significantly lower recurrence rate could be found in patients who were initially treated with an external rotation brace (20 % recurrence rate in the external rotation group vs. 38 % in the internal rotation group). Several other studies have been published since the initial reports by Itoi et al, investigating the immobilization period [4] and the amount of external rotation that is required to effectively reduce the labroligamentous complex (LLC) [5].…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…In comparison with traditional immobilization in internal rotation, this new method was assumed to reduce the recurrence rate after a first-time traumatic anterior shoulder dislocation. These findings were later supported by Itoi et al [2,3] in an MRI study (2001) and in a randomized controlled study (2007) in which a significantly lower recurrence rate could be found in patients who were initially treated with an external rotation brace (20 % recurrence rate in the external rotation group vs. 38 % in the internal rotation group). Several other studies have been published since the initial reports by Itoi et al, investigating the immobilization period [4] and the amount of external rotation that is required to effectively reduce the labroligamentous complex (LLC) [5].…”
Section: Introductionmentioning
confidence: 70%
“…An expanded prospective study was published by Itoi et al in 2007. In this trial, the rate of recurrence was significantly lower within the group of bracing in external rotation compared to the group with internal rotation with an average follow-up of 25.6 months ( Table 2).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A subsequent short-term clinical study revealed decreased recurrence rates in patients immobilized in external rotation compared to those immobilized in internal rotation. 12 After 3 weeks of immobilization, the external rotation group had a recurrence rate of 26%, while the recurrence rate for those in the internal rotation group was 42%, with a relative risk reduction of 46% in patients younger than 30 years.…”
Section: Etiology and Epidemiologymentioning
confidence: 91%